Face mask usage during Covid-19 pandemic: prevalence and factors associated in Malaysian Medical School - Mohamad Zainal, Nurul Hayati; Abas, Razif; Mohamad Asri, Siti Fadziyah; Sivakumar, Aishwarya; Ibrahim, Ahmad Muaz; Azhar, Dayana Aida; Mohd Nor, Nurul Huda (Akademi Sains Malaysia, 2021)
Coronavirus disease 2019 (COVID-19) is a contagious disease caused by a newly discovered coronavirus strain. Anxiety, anticipation, and lack of knowledge in the previous experience on severe acute respiratory syndrome (SARS) and influenza A virus subtype H1N1 (H1N1) pandemic have a substantial impact on significant public health behaviours including wearing face mask in public spaces. We investigate the prevalence of face mask usage and its associated factors during COVID19 amongst students and staff of the Faculty of Medicine and Health Sciences (FMHS), Universiti Putra Malaysia (UPM). Using a cross-sectional study, 220 respondents participated in an electronic version of a self-administered questionnaire. Analyses were performed using the Chi-square test, IBM SPSS Statistics 25, with statistical significance at p<0.05. Out of the 220 respondents, 197 (89.5%) reported that they wore face masks all the time. Most of the respondents (90.3%) had a high level of precautionary measures against COVID-19, 89.6% selected the internet as their source of information and 90.9% had a good attitude level towards measures against COVID-19. There were significant associations between hygienic practices (p=0.001), source of information (internet) (p=0.025), and attitude towards COVID-19 (p=0.001) with face mask usage. This study demonstrated a high prevalence (89.5%) of face mask usage during the COVID-19 outbreak.